ACTIVE DEFORMATION IN ZAGROS-MAKRAN TRANSITION ZONE INFERRED FROM GPS MEASUREMENTS - Bayer R.; Chery J.; Vernant Ph.; Masson F.; Doerflinger E.; Tatar M.; Abbassi M.; Nilforoushan F.; Regard V.; Bellier O. (My University, 2006)
The Bandar Abbas-Strait of Hormuz zone is considered as a transition between the Zagros collision and the Makran oceanic subduction. We used GPS network measurements collected in 2000 and 2002 to better understand the distribution of the deformation between the collision zone and the Makran subduction. Analysing the GPS velocities, we show that transfer of the deformation is mainly accommodated along the NNW-SSE-trending reverse right-lateral Zendan-Minab-Palami (ZMP) fault system. The rate is estimated to 10 ± 3 mm yr-1 near the faults. Assuming that the ZMP fault system transfers the motion between the Makran-Lut Block and the Arabian plate, we estimate to 15 mm yr-1 and 6 mm yr-1, respectively, the dextral strike-slip and shortening components of the long-term transpressive displacement. Our geodetic measurements suggest also a 10-15 km locking depth for the ZMP fault system. radial velocity pattern and the orientation of compressive strain axes around the straight of Hormuz is probably the consequence of the subducting Musandam promontory. The N-S Jiroft-Sabzevaran (JS) fault system prolongates southwards the dextral shear motion of the Nayband-Gowk (NG) fault system at an apparent rate of 3.1 ± 2.5 mm yr-1. The change from strong to weak coupling for underthrusting the Arabian plate beneath the Zagros (strong) and the Makran (weak) may explain the dextral motion along the ZMP, JS/NG and Neh-Zahedan fault systems which transfer the convergence from a broad zone in the western Iran (Zagros, Tabriz fault system, Alborz, Caucasus and Caspian sea surroundings) to Makran subduction. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: ACTIVE DEFORMATION; COLLISION; GPS; MAKRAN; SUBDUCTION; ZAGROS